2019
DOI: 10.1080/07853890.2019.1614657
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year experience with transcatheter and surgical aortic valve replacement in Finland

Abstract: Aim: We investigated the outcomes of transcatheter (TAVR) and surgical aortic valve replacement (SAVR) in Finland during the last decade. Methods: The nationwide FinnValve registry included data from 6463 patients who underwent TAVR or SAVR with a bioprosthesis for aortic stenosis from 2008 to 2017. Results: The annual number of treated patients increased threefold during the study period. Thirty-day mortality declined from 4.8% to 1.2% for TAVR (p ¼ .011) and from 4.1% to 1.8% for SAVR (p ¼ .048). Two-year su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
(46 reference statements)
3
18
0
Order By: Relevance
“…The inclusion criteria for this study were (1) transfemoral TAVR for AS with or without aortic valve regurgitation; (2) patients aged >18 years; and (3) primary TAVR with or without concomitant coronary revascularization. The exclusion criteria were (1) prior TAVR or surgical intervention on the aortic valve; (2) transcatheter or surgical procedure for isolated aortic valve regurgitation; (3) acute endocarditis; and (4) TAVR performed through other than transfemoral access.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…The inclusion criteria for this study were (1) transfemoral TAVR for AS with or without aortic valve regurgitation; (2) patients aged >18 years; and (3) primary TAVR with or without concomitant coronary revascularization. The exclusion criteria were (1) prior TAVR or surgical intervention on the aortic valve; (2) transcatheter or surgical procedure for isolated aortic valve regurgitation; (3) acute endocarditis; and (4) TAVR performed through other than transfemoral access.…”
Section: Study Populationmentioning
confidence: 99%
“…RECENT STUDIES FROM nationwide registries reported a three-to six-fold increase in the use of transcatheter aortic valve replacement (TAVR) procedures for severe aortic stenosis (AS) in previous years. 1,2 The widespread use of TAVR paralleled with a larger number of patients being referred for invasive treatment of AS with a documented improvement of early and midterm survival. 2 Interestingly, these studies showed a significant decrease in the rates of red blood cell (RBC) transfusion after TAVR during the most recent years.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The FinnValve registry is a Finnish multicenter nationwide registry including retrospectively collected data from consecutive patients undergoing TAVR or surgical aortic valve replacement with a bioprosthesis for severe AS at all five Finnish university hospitals (Turku, Helsinki, Kuopio, Tampere and Oulu) between January 2008 and November 2017 (Clinical trial registration: ClinicalTrials.gov Identifier: NCT03385915) [12]. The study protocol was approved by the Institutional Review Boards of all participating centers and the Ethics Committee of the National Institute for Health and Welfare.…”
Section: Study Populationmentioning
confidence: 99%